1970
DOI: 10.1111/j.1471-4159.1970.tb02247.x
|View full text |Cite
|
Sign up to set email alerts
|

INTERRELATIONSHIPS BETWEEN PYRIDOXAL PHOSPHATE AND PYRIDOXAL KINASE IN RABBIT BRAIN1

Abstract: —An inverse relationship was demonstrable between the concentration of pyridoxal phosphate and the activity of pyridoxal kinase in rabbit brain. The administration of pyridoxine elevated the concentration of pyridoxal phosphate and decreased the activity of pyridoxal kinase. Conversely, the administration of deoxypyridoxine decreased the concentration of pyridoxal phosphate and increased the activity of pyridoxal kinase. The increase in the activity of pyridoxal kinase by deoxypyridoxine was blocked by actinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…In the course of these studies, it was found that the behavior of the perfused livers differed with the state of vitamin B. nutrition of the donor animals (Figs. 2-5 as has been previously demonstrated in brain tissue (26).…”
Section: An4)supporting
confidence: 65%
“…In the course of these studies, it was found that the behavior of the perfused livers differed with the state of vitamin B. nutrition of the donor animals (Figs. 2-5 as has been previously demonstrated in brain tissue (26).…”
Section: An4)supporting
confidence: 65%
“…3 and 9). The importance of the phosphatase as a regulator of PLP concentrations in tissues has not been fully appreciated in the past and considerations of regulatory mechanisms have centered primarily on modes of inhibition or inactivation of the kinase enzyme (19,26). The control mechanism based on pyridoxal as a regulatory molecule (19) probably does not apply to man since our findings indicated that pyridoxal does not inactivate the pyridoxal kinase of erythrocytes.…”
Section: Discussionmentioning
confidence: 66%
“…Pyridoxal kinase activity in brain changes with dietary intake. Spector and Shikuma (1978) suggested that a report of a negative correlation between pyridoxal phosphate and pyridoxal kinase in rabbit brain (Ebadi et al 1970) was due to errors caused by using pyridoxal rather than pyridoxine as the substrate for analyzing kinase activity. When various areas of normal rat brain were compared, there was a positive correlation between pyridoxal kinase activity and pyridoxal phosphate concentration (Ebadi and Bifano 1978).…”
Section: Regulation Of Vitamin B-6 Metabolismmentioning
confidence: 99%
“…Unfortunately, the distinction is frequently ignored in the literature. Ebadi et al (1970) noted that pyridoxal kinase activity was increased in the presence of deoxypyridoxine and that the increase was prevented by actinomycin D or puromycin. While Ebadi et al (1970) interpreted the results as an inverse relationship between pyridoxal phosphate and kinase activity, we suspect that since deoxypyridoxine is a substrate for the kinase, the presence of deoxypyridoxine may have stimulated the increased synthesis of pyridoxal kinase.…”
Section: Regulation Of Vitamin B-6 Metabolismmentioning
confidence: 99%
See 1 more Smart Citation